Training and Assistance to Enhance Toilet Training Success among Children Aged 2–3 Years in Daycare Centers - Amelisa Wulandari; Lilis Kurniati; Nur Hanifa (CV Berkah Syahdin Trust, 2025)
Background: Early childhood is a critical stage for developing independence in self-care; however, many children aged 2–3 years still experience difficulties in recognizing and practicing proper toilet training, highlighting the need for interactive and developmentally appropriate approaches. Aims: This community service program aims to enhance the knowledge and success of toilet training for children aged 2–3 years through interactive and engaging activities. Methods: This program employed a Participatory Action Research (PAR) approach consisting of planning, action, observation, and reflection stages. The planning stage involved identifying toilet training problems, conducting discussions with caregivers and parents, and designing interactive activities. The action stage focused on implementing toilet training practices through engaging and context-based activities. The observation stage involved monitoring and documenting children’s progress during the training process. The reflection stage included evaluating outcomes and identifying areas for improvement. Data were collected through observation and documentation and analyzed descriptively. Results: The results indicate improvements in children’s toilet training abilities, including increased independence, better understanding of toileting routines, and more consistent behavior. Children showed progress in recognizing the need to use the toilet and performing toileting activities with reduced assistance. Additionally, caregivers and parents reported positive behavioral changes and increased awareness of effective toilet training strategies. Conclusion: Interactive and context-based toilet training activities are effective in improving toilet training success among young children. The integration of structured activities, caregiver involvement, and continuous monitoring creates a supportive learning environment that promotes independence. This approach can be applied as an alternative method in early childhood care settings to support the development of essential self-care skills.